PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTU VISUAL GAMBAR TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GANJIL SMP NEGERI 1 PUNGGUR - Wahono Wahono; Ningrum Ningrum (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The problem in this study is "There are still many students who have not completed the Integrated Social Studies learning outcomes of class VIII in the odd semester of SMP Negeri 1 Punggur 2018/2019 Academic Year". The purpose of this study was to determine the effect of using the Model Visual Based Learning Problem on Integrated Social Studies Learning Outcomes of Class VIII Odd Semesters of State Middle School 1 Punggur Academic Year 2018/2019. Then the hypothesis in this study is as follows: "There is a positive influence on the use of the Model Problem Based Learning Helps Visual Images of Integrated Social Studies Learning Outcomes of Class VIII Odd Semesters of State Junior High School 1 Punggur 2018/2019 Academic Year". The design used in this study was an experiment. Experimental research methods can be interpreted as research methods that will be used to find the effect of certain treatments on others under controlled conditions. The experimental method used was quasi experimental design in the form of nonequivalent control group design. Because in this design it cannot control the external variables that affect the implementation of the experiment. Based on the results of these studies, the hypothesis is accepted, because the value of tcount> t table can be seen in the list of G, on the list of significant 5% which is 4.30> 1.70. Thus the results of the calculation in this study by using visual aided problem based learning model were 43%. Students who were declared complete with KKM (70) after treatment were 28 students or 82.35% and students who were declared incomplete were 6 students or 17.65%. Thus it shows that the Visual Image-Assisted Problem Based Learning Model has a positive influence on the Integrated Social Studies learning outcomes of class VIII Odd Semesters of State Middle School 1 Punggur Academic Year 2018/2019. Keywords: Visual Assisted Problem Based Learning Models, Learning Outcomes of Social Sciences Students.